Photoinduced birefringence in azopolymer doped with Au nanoparticles. (October 2019) - Nazarova, D; Nedelchev, L; Stoykova, E; Blagoeva, B; Mateev, G; Karashanova, D; Georgieva, B; Kostadinova, D
Abstract: A study of the photoinduced birefringence in nanocomposite thin films of the azopolymer PAZO (poly[1-[4-(3-carboxy-4-hydroxyphenylazo)benzenesulfonamido]-1, 2-ethanediyl, sodium salt]) doped with gold (Au) nanoparticles (NPs) is presented. The NPs are with a spherical shape and mean size 10 nm. Transmission electron microscopy (TEM) and Dynamic Light Scattering (DLS) analyses of the particles have also been made. Samples were prepared with five different concentrations of the NPs in the azopolymer films varying from 0 (non-doped azopolymer film) to 4 a.u. (1 a.u. = 0.015 wt %). Birefringence was induced by a He-Cd laser with a wavelength 442 nm and measured with probe Diode Pumped Solid State (DPSS) laser at 635 nm. An increase of the photoinduced birefringence in doped azopolymer nanocomposite films compared to samples of undoped azopolymers was observed. The maximal enhancement was achieved for films with 2 a.u. of Au NPs.